Modification of neutrophil functional capacity under cold and electromagnetic radiation influence - Litovchenko, Olena L.; Zub, Ksenia O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 165.